1988
DOI: 10.2514/3.9991
|View full text |Cite
|
Sign up to set email alerts
|

Turbularization of an acoustic boundary layer on a transpiring surface

Abstract: Turbularization of an acoustic boundary layer (Stokes layer) on impermeable and permeable surfaces is analytically considered. The theoretical approach utilizes a second-order closure model of turbulence. Both an approximate, closed-form solution and a more comprehensive finite-difference solution of the time-dependent, parabolic, one-dimensional governing equations are obtained. For simple acoustic boundary layers on impermeable surfaces, both the approximate solution and the numerical results for the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…In support of theoretical approximations, equally appreciable laminar and turbulent segments have been identified in a series of studies conducted by Apte and Yang [39,40], Liou and Lien [41], and Beddini and Roberts [42,43]. These teams have simultaneously concurred that turbulent simulations in the downstream sections of long SRMs tended to exhibit convincing similarities with corresponding laminar flow results.…”
Section: Practicality and Significancementioning
confidence: 65%
See 1 more Smart Citation
“…In support of theoretical approximations, equally appreciable laminar and turbulent segments have been identified in a series of studies conducted by Apte and Yang [39,40], Liou and Lien [41], and Beddini and Roberts [42,43]. These teams have simultaneously concurred that turbulent simulations in the downstream sections of long SRMs tended to exhibit convincing similarities with corresponding laminar flow results.…”
Section: Practicality and Significancementioning
confidence: 65%
“…Equations (36)(37)(38)(39)(40)(41)(42) constitute the most basic rotational model that can be used to describe the streamtube motion in a circular hybrid chamber. Despite being inviscid and incompressible, it satisfies no-slip at the sidewall and its headwall injection constant may be adjusted to mimic the bulk gasified motion in an actual system.…”
Section: Sinusoidal Headwall Injectionmentioning
confidence: 99%
“…The most noteworthy achievements of these studies has been the identification of specific sources of instability, such as parietal, obstacle, and angle vortex shedding, clarifying the connection between the stability eigenmodes and the reported frequencies, delineating the salient acoustic frequencies and pressure shifts, and elucidating the inconsistencies between techniques that entail perturbations of the primitive variables and those that rely on stream function formulations. [3][4][5][6] Their work has also helped to explain the spatial evolution of disturbances in simulated porous channels and tubes, which mimic the flowfield in solid rocket motors. In fact, a collection of lab-scale firings 18 and cold-flow data acquired using two carefully designed experimental facilities (i.e., VECLA and VALDO) have shown practical agreement with the findings obtained through hydrodynamic stability models, thus proving their viability in simulating certain aspects of unsteady rocket chamber flows.…”
Section: Introductionmentioning
confidence: 97%
“…2 In terms of turbulence characterization in simulated rocket configurations, works by Beddini, 3 Beddini and Roberts, 4 Lee and Beddini,5,6 Apte and Yang, [7][8][9] Wasistho, Balachandar and Moser, 10 and numerous others have contributed significant advancements to our understanding of the corresponding unsteady flowfield. More recent studies by Casalis, Avalon, and Pineau, 11 Griffond, Casalis and Pineau, 12 Ugurtas et al, 13 Griffond and Casalis,14,15 Féraille and Casalis, 16 and Fabignon et al 17 have paid special attention to different hydrodynamic stability models and their ability to predict with varying degrees of accuracy the oscillatory motions observed in solid rocket motors.…”
Section: Introductionmentioning
confidence: 99%
“…So far, these studies have revealed the basic inconsistencies between techniques that entail perturbations of the primitive variables and those that rely on streamfunction formulations. [10][11][12][13] In addition, they have helped to explain the roles of the headwall boundary layer and the spatial evolution of disturbances in simulated porous channels and tubes, which mimic the flowfield in solid rocket motors (SRM). Overall, the ensuing theoretical findings obtained through hydrodynamic stability analyses have been carefully supported by cold-flow measurements acquired using two experimental facilities coined VECLA (Veine d'Etude de la Couche Limite Acoustique) and VALDO (Veine Axisymmétrique pour Limiter le Développement des Oscillations), as well as laboratory-scale firings.…”
Section: Introductionmentioning
confidence: 99%